A Core Omnigenic Non-coding Trait Governing Dex-Induced Osteoporotic Effects Identified Without DEXA - Li Lu (Frontiers Media S.A., 2021)
Iatrogenic glucocorticoid (GC)-induced osteoporosis (GIO) is an idiosyncratic form of secondary osteoporosis. Genetic predisposition among individuals may give rise to variant degree of phenotypic changes but there has yet been a documented unified pathway to explain the idiosyncrasy. In this study, we argue that the susceptibility to epigenetic changes governing molecular cross talks along the BMP and PI3K/Akt pathway may underline how genetic background dictate GC-induced bone loss. Concordantly, osteoblasts from BALB/c or C57BL/6 neonatal mice were treated with dexamethasone for transcriptome profiling. Furthermore, we also confirmed that GC-pre-conditioned mesenchymal stem cells (MSCs) would give rise to defective osteogenesis by instigating epigenetic changes which affected the accessibility of enhancer marks. In line with these epigenetic changes, we propose that GC modulates a key regulatory network involving the scavenger receptor Cd36 in osteoblasts pre-conditioning pharmacological idiosyncrasy in GIO.